Skid control of small electric vehicle with hydraulic-mechanical hybrid brake system - Mohamad Heerwan, Peeie (2012)
In recent years, environmental problems have spread around the world. To cope with this problem, electric vehicle have widely used.As we know, the fundamental of a driving method for electric vehicle can be separate into two types, which are one motor system and in-wheel motor system. There are many advantages by using in wheel motors such as motors torque generation is faster and accurate, motors can be installed in 2 or 4 wheels, and motors torque can be known precisely.For a small electric vehicle, in-wheel motor is more suitable than one motor.Although small electric vehicle have a great in-wheel motor,the safety equipment of small electric vehicle is not sufficient because it only contains seat belts as safety equipment. The hydraulic unit of Antilock Brake System (ABS) cannot install into small electric vehicle because there is no space. Therefore, small electric vehicles employ a mechanical brake system rather than a hydraulic brake system. The demerit of the mechanical brake system is the stiffness of the system is smaller than the hydraulic brake system and the response performance of the braking force also low. As such, small electric vehicles may be considered to provide insufficient safety.